News as a Cultural Mirror: Historically Black Newspapers Reflecting Public Views of Loving v. Virginia (1967). (10th December 2015) - Ware, Jennifer; Zeldes, Geri Alumit; Hoewe, Jennifer
Abstract : This study examined seven historically Black newspapers' coverage of the landmark Supreme Court case Loving v. Virginia (1967), which overturned anti‐miscegenation laws that prevented non‐White individuals from marrying White individuals. A content analysis of frames and source usage within 31 news stories about the case indicated that about half of the stories ( N = 14) advocated for the Lovings and a small number ( N = 1) advocated for the State of Virginia; the remaining stories were either informational ( N = 7) or objectivist ( N = 9). Because the media is said to be a cultural mirror of public opinion, the results of this study may indicate the public's views on the issue of intermarriage laws. This study's findings also showed that historically Black newspapers agreed with their mainstream counterparts more than they disagreed.